2016
DOI: 10.2355/tetsutohagane.tetsu-2015-064
|View full text |Cite
|
Sign up to set email alerts
|

Development of Analytical Methods for Free-MgO in Steelmaking Slag

Abstract: Steelmaking slags have been widely used as aggregate for road and civil engineering. The slags sometimes expand as a result of hydration, which may cause evolution of cracks at surfaces of roads when used as aggregate. Free magnesium oxide (free-MgO) in the slags is a potential cause of the expansion as well as free calcium oxide is. Thus, analytical methods to determine the free-MgO in the slag have been required for the accurate evaluation of the expansion. We present an accurate method to determine the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There is no commonly applied MgO equivalent to the ethylene glycol test for CaO, so free MgO can be difficult to estimate. Some selective extraction methods have been proposed, such as with potassium dichromate [287], ammonium nitrate [288], or ethylene glycol with iodine and ethanol [289,290], while other studies proposed solid-state 25 Mg nuclear magnetic resonance spectroscopy [291] or petrographic methods [292], but their data are limited. However, the free MgO content is very important to estimate, because the MgO reaction with water is a longer-term reaction than CaO, resulting in the potential for unexpected failures at later ages.…”
Section: Free Mgo Contentmentioning
confidence: 99%
“…There is no commonly applied MgO equivalent to the ethylene glycol test for CaO, so free MgO can be difficult to estimate. Some selective extraction methods have been proposed, such as with potassium dichromate [287], ammonium nitrate [288], or ethylene glycol with iodine and ethanol [289,290], while other studies proposed solid-state 25 Mg nuclear magnetic resonance spectroscopy [291] or petrographic methods [292], but their data are limited. However, the free MgO content is very important to estimate, because the MgO reaction with water is a longer-term reaction than CaO, resulting in the potential for unexpected failures at later ages.…”
Section: Free Mgo Contentmentioning
confidence: 99%
“…14) Although it is possible to determine the free lime content, the expansion characteristics and related mechanisms of slag have not been sufficiently clarified, and there is a poor correlation between the quantitative free lime content and expansion characteristics. It is known that the hydration of calcium silicate, calcium aluminate, and magnesium oxide [15][16][17] is not negligible. Furthermore, divalent metal oxides such as FeO and MnO can form solid solutions in CaO, and the hydration reactivity of free lime changes depending on the solid solubility (the amount of divalent metal oxide in the solid solution).…”
Section: Change Of State Of Lime Phase and Inhibition Of Hydration Reaction By Coexisting Oxides In Steelmaking Slagmentioning
confidence: 99%
“…The angles of the diffraction lines were located near the halfway point between those of MgO and FeO, and they were mixed in a nearly equal ratio. Similar to CaO, MgO is known to cause hydration expansion as free magnesia [15][16][17] and has a lower hydration activity than CaO, and hydration proceeds slowly because of the chemical properties of MgO. In addition to the above, it can be understood that the facile formation of a solid solution containing a high concentration of FeO also effectively suppresses the hydration activity.…”
Section: Crystal Phases In Slag and Their Distributionsmentioning
confidence: 99%
“…Similar to free CaO, a crystallized MgO precipitated during cooling is observed along with undissolved MgO in steelmaking slag, and the content of divalent metal oxides MO (FeO, MnO and CaO) solid-solved in crystallized MgO are considered to have an effect on the hydration reactivity of MgO. Hanada et al [28] reported that the solid-solved component in crystallized MgO affected the chemically analyzed free MgO concentration [28], but they did not investigate its effect on the hydration reactivity of MgO.…”
Section: Introductionmentioning
confidence: 99%